Missense Mutations of Codon 116 in the SOD1 Gene Cause Rapid Progressive Familial ALS and Predict Short Viability With PMA Phenotype - Wen, Xinmei; Zhu, Wenjia; Xia, Nan L.; Li, Qianwen; Di, Li; Zhang, Shu; Chen, Hai; Lu, Yan; Wang, Min; Xu, Min; Wang, Suobin; Shen, Xin-Ming; et al. (Frontiers in Genetics, 2021)
Amyotrophic lateral sclerosis (ALS) is the most common form of motor neuron disease, characterized by great variety of both clinical presentations and genetic causes. Previous studies had identified two different missense mutations in SOD1 (p.R116C and p.R116G) causing familial ALS. In this study, we report a novel heterozygous missense mutation in the SOD1 gene (p.R116S) in a family with inherited ALS manifested as fast deteriorating pure lower motor neuron symptoms. The patient displayed similar clinical picture and prognostic value to previous reported cases with different R116 substitution mutations. Modeling of all R116 substitutions in the resolved SOD1 protein structure revealed a shared mechanism with destroyed hydrogen bonds between R116 and other two residues, which might lead to protein unfolding and oligomer formation, ultimately conferring neurotoxicity.